J11 The pre-season variation in physical performance of an elite level female cricket squad - Morris, Bethany; Finlay, Mitchell (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Cricket is as an endurance sport comprising intermittent bursts of speed and power. The introduction of new formats of varying duration and intensity means the physical demands of cricket can vary. Regardless of format, it is agreed that the high-intensity efforts involved in elite level cricket require high levels of lower-body strength and power, and upper-body strength and rotational power (Herridge et al., 2020, J Strength Cond Res, 34, 2285-2293). Previous research has demonstrated that physical qualities can vary throughout seasonal periods (Herridge et al., 2020; Carr et al., 2017, Int J Sports Phys Perf, 12, 50-55) due to training effects. Based on this small body of research, physical performance in common performance tests seem to plateau or decrease across a season, whereas performance tends to increase in the off- and pre-season. This suggests that the off- and pre-season are key phases whereby practitioners can positively influence physical qualities of cricketers. However, despite the growth of the female format, the only studies to have explored the variations in physical qualities have been focused on male cricket. Therefore, the aim of this study was to assess the pre-seasonal variation in the physical performance of female cricket players. 10 elite level female cricketers (age = 23 ± 4 years, stature = 166 ± 7 cm, mass = 71 ± 7 kg) performed a testing battery at 3 points during the pre-season (October – Time point (TP) 1, December – TP 2, February – TP 3). Three trials of bilateral countermovement jumps (CMJ), unilateral CMJ (UCMJ), squat jump (SJ), 10/5 repeated jump test (RJT), Nordic hamstring test (NHT), and isometric mid-thigh pull (IMTP). Data were analysed via a repeated measure ANOVA with post-hoc analysis where appropriate. Improvements (P < 0.005) were evident in peak CMJ and mean jump height, right UCMJ peak jump height, and peak and mean force in the left and right leg in the NHT. Non-significant improvements were seen in several other metrics across time points. The ES for differences in physical tests between T1 and T2 ranged from ES = −0.09 to 0.61, T1 and T3 ranged from ES = −0.05 to 1.04, and T2 and T3 ranged from ES = −0.03 to 0.83. The results of this study showed select strength-power metrics in elite female cricketers significantly changed across time points during the pre-season, suggesting desirable adaptations to strength-based training phases.